Simulation of steady mixed convection in a lid-driven cavity filled with newtonian fluid by finite volume method - Abu Bakar, Norhaliza (2019)
The steady mixed convection flow in a lid-driven cavity was simulated. The cavity was filled with a Newtonian fluid, both vertical walls are adiabatic, while the horizontal walls were either fixed cold and uniformly/oscillatory heated. Firstly, the effect of internal heat generation or absorption on the fluid flow and heat transfer behaviours was studied. The moving upper wall was uniformly heated while the bottom wall was kept cold. The effect of magnetic field on fluid flow and heat transfer was analysed in the second problem. An inclined magnetic field was considered in the third problem. In the fourth problem, the flow inside an inclined cavity was simulated, where the top wall was subjected to an heated oscillating temperature. Finally, the mixed convection within an inclined cavity with the presence of an inclined magnetic field was studied. The dimensionless governing equations were formulated by using appropriate reference variables. These equations were solved using the finite volume method. The convection-diffusion terms were discretized using the power law scheme while the pressure and velocity components were coupled using the SIMPLE algorithms. The resultant matrices were then solved iteratively using the Tri- Diagonal Matrix Algorithm coded in FORTRAN90. The present solutions obtained were then compared with those of previous studies and a good agreement was found. The numerical results were presented in the forms of isotherm and streamline. It was found that the heat transfer rate in an inclined cavity increased mildly for both forced convection dominated and mixed convection dominated regimes. However, for natural convection dominated regime, the heat transfer rate decreased when the inclination angle was 30◦ and increased when the inclination angles reached 60◦. The presence of external forces would affect the local heat transfer and fluid flow behaviours significantly.